O trabalho escravo e a ocorrência da escravidão rural contemporânea no Rio Grande do Sul - Mourad, Leonice Aparecida de Fatima Alves Pereira (2015)
This research has as its central theme the study of contemporary rural slave labor in RS, with emphasis on forestry and fruit culture, activities with the highest incidence of this type of exploration work, recognized by the ILO as forced labor, characterized by debt slavery. We focused on the identification, description and questioning the role of the Federal Government, with special emphasis on the MTE performance and Special Groups Furniture that, under national law, have the task of fighting and rebuke of modern-day slavery. In terms of methodology, we used the assumptions of bibliographical and documentary research, based on national and international legislation as well as the data provided by the Federal Government, State Government, CPT, ILO, MPT-RS and other agencies. We also use, as a secondary source, data from studies on the enslaved worker's profile and those who use slave labor. It should be noted that contemporary rural slavery in Brazil and Rio Grande do Sul is closely related with the typical spatial arrangements of a sharp technological development (horticulture and forestry accuracy), which is used, even peripherally, of the forced labor populations characterized by a marked social and economic vulnerability, which enhance their recruitment, so to reify workers in a flagrant violation of the human rights.